2021
DOI: 10.1007/s00253-021-11350-7
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes: the novel sources for plant terpenoid biosynthesis

Abstract: Terpenoids are natural compounds predominantly present in plants. They have many pharmaceutical and/or nutritional functions, and have been widely applied in medical, food, and cosmetics industries. Recently, terpenoids have been used in the clinical treatment of COVID-19 due to the good antiviral activities. The increasing demand for terpenoids in international markets poses a serious threat to many plant species. For environmentally sustainable development, microbial cell factories have been utilized as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
(66 reference statements)
2
17
0
Order By: Relevance
“…These monoterpenoid compounds were produced in low percent-ages due to the poor catalytic activity of plant derived enzymes in the endophytic system (Sun et al, 2019). The monoterpenoid compounds and their precursors are known to express antioxidant, anticancer and antimicrobial activities [7,58,59]. The present study revealed that the endophytic fungus F1 1 (C. cladosporioides) and the host plant share common Mevalonate (MVA) and Phenylpropanoid (PP) pathways as also documented in earlier studies [7,50].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These monoterpenoid compounds were produced in low percent-ages due to the poor catalytic activity of plant derived enzymes in the endophytic system (Sun et al, 2019). The monoterpenoid compounds and their precursors are known to express antioxidant, anticancer and antimicrobial activities [7,58,59]. The present study revealed that the endophytic fungus F1 1 (C. cladosporioides) and the host plant share common Mevalonate (MVA) and Phenylpropanoid (PP) pathways as also documented in earlier studies [7,50].…”
Section: Discussionsupporting
confidence: 83%
“…The monoterpenoid compounds and their precursors are known to express antioxidant, anticancer and antimicrobial activities [7,58,59]. The present study revealed that the endophytic fungus F1 1 (C. cladosporioides) and the host plant share common Mevalonate (MVA) and Phenylpropanoid (PP) pathways as also documented in earlier studies [7,50].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Several well-characterized natural compounds have been documented for their antimicrobial, anti-inflammatory and other beneficial effects on humans and animals thereby offering promising sources for drug development (Clark, 1996 ; El Sayed, 2000 ). Advancement in the synthetic biology also has accelerated the mass production of natural compounds (Chen et al, 2021 ). The ethno-medical literature has listed various herbal plants for their appealing antiviral activity (Ganjhu et al, 2015 ; Mukhtar et al, 2008 ; Potroz & Cho, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes are considered as potential alternatives for terpenoid bioproduction due to their long-term harmony and coevolution with plants ( Venugopalan and Srivastava, 2015 ). However, the main obstacles to the commercialization of endophytes are the low inner catalytic activity of plant-derived enzymes, lack of gene information regarding the biosynthesis pathway, and the silence of SM gene clusters ( Gupta et al, 2020 ; Qiao et al, 2020 ; Chen et al, 2021 ). Modern RNA-sequencing methods enable researchers to gain a quick and comprehensive understanding of the plant-derived compound biosynthesis pathway in endophytes, and determine the association between each individual gene and a phenotype ( Zhang et al, 2015 ; Qiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%